The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2478/rtuect-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Cost of Biomass from Post-Mining Peaty Lands for Pellet Fabrication

Abstract: Post-mining peaty lands were formed as a result of peat extraction on drainage wetlands areas. After peat extraction has finished, the biggest problem is to use these lands for other purposes. This type of soil is very heterogenic, poorly drained, with massive structure and poor contents of nutrients. Thus it is very problematic to grow traditional agricultural crops that have special requirements for soil fertility on those areas. The area of post-mining peaty lands in Belarus alone is about 200 000 hectares.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…As a result, the ash had a positive effect on willow growing, especially in the second year after application (Table 3). In our experiment, the ash had a positive effect with dose application 1.0 and 1.5 mg dry mass ha -1 (Parka et al, 2005;Rodzkin et al, 2018;Rodzkin et al, 2019). Another study reported the positive effect of wood ash application on the soil acidity and the size of willow stems, but not on biomass production because the mean number of stems was significantly smaller in the ash-treated plots than in the control plots (Lazdina et al, 2011).…”
Section: Peat Ash Application On Ef2supporting
confidence: 41%
“…As a result, the ash had a positive effect on willow growing, especially in the second year after application (Table 3). In our experiment, the ash had a positive effect with dose application 1.0 and 1.5 mg dry mass ha -1 (Parka et al, 2005;Rodzkin et al, 2018;Rodzkin et al, 2019). Another study reported the positive effect of wood ash application on the soil acidity and the size of willow stems, but not on biomass production because the mean number of stems was significantly smaller in the ash-treated plots than in the control plots (Lazdina et al, 2011).…”
Section: Peat Ash Application On Ef2supporting
confidence: 41%
“…It means that radionuclide pollution didn't influence dramatically on willow productivity. Yield of willow which growing on radionuclide and heavy metals polluted soils is close to ordinary yield for mineral fertile soils [53], [54].…”
Section: Environmental and Climate Technologiesmentioning
confidence: 99%
“…Both ensuring compliance with the regulation and pursuing the eradication of the invasive species require financial means, however the new vision of the 167 invasive plant management system would actually ensure financial gains. Similarly to other studies, that aim to add value to low quality and underused biomass, such as common reed, cattail, sedges [4], potato peels [5], forest residue [6] and agricultural waste (grasses, vegetable silage, etc.) [7].…”
Section: Introductionmentioning
confidence: 99%